2018
DOI: 10.1007/s13304-018-0589-2
|View full text |Cite
|
Sign up to set email alerts
|

Barbed vs conventional sutures in bariatric surgery: a propensity score analysis from a high-volume center

Abstract: The use of barbed sutures for constructing an anastomosis is favoured by a few bariatric surgeons as compared to conventional sutures. The aim of this study is to assess safety and efficacy of barbed sutures to close the gastric pouch-jejunal anastomosis (GPJA) in laparoscopic gastric bypass (Roux-en-Y gastric bypass-RYGB, and One-Anastomosis gastric bypass-OAGB) using propensity score-matching (PSM) analysis. A retrospective analysis of patients who underwent primary laparoscopic gastric bypasses between Janu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 41 publications
1
29
0
Order By: Relevance
“…The literature search identified nine studies that were suitable for inclusion in the analysis (two randomised trials, 14,15 six cohort studies, [16][17][18][19][20][21] and one population based cohort study). 22 Figure 1 demonstrates the preferred reporting items for systematic reviews and meta-analyses flowchart for the literature search.…”
Section: Resultsmentioning
confidence: 99%
“…The literature search identified nine studies that were suitable for inclusion in the analysis (two randomised trials, 14,15 six cohort studies, [16][17][18][19][20][21] and one population based cohort study). 22 Figure 1 demonstrates the preferred reporting items for systematic reviews and meta-analyses flowchart for the literature search.…”
Section: Resultsmentioning
confidence: 99%
“…In the current literature, the safety and efficacy of barbed suture has been demonstrated in many surgical fields [8, 9, 10, 11, 12, 13], but less is known in digestive surgery, where its efficacy and safety has been demonstrated mainly in bariatric surgery [36, 37, 38].…”
Section: Discussionmentioning
confidence: 99%
“…Another possible advantage of using the barbed suture is a gain in time; however, we cannot judge this due to the lack of a control group. Vidarsson et al 2017 [7] and Pennestri et al 2018 [8] describe a significant time gain using barbed sutures in laparoscopic RYGB procedures, whereas Gys et al 2017 found significant time benefit only for the anastomosis itself, not for the total procedure time [6]. Compared to a historical laparoscopic RYGB cohort [12], the mean operative time with the surgical robot was about 10 min shorter.…”
Section: Discussionmentioning
confidence: 99%
“…Self-fixing barbed suture material makes the laparoscopic knot obsolete and promises a constant thread tension after a single tightening of the barbed suture material. Studies have proven the safety and efficacy of this special suture material in laparoscopy [58]. Gys et al reported a comparable operative time with a shorter anastomosis time in a randomized controlled study [5, 6], while Vidarsson et al evaluated a cohort of 25,000 patients and found indications of a shortening of the total operating time, also with comparable safety [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation